Natural Cavities in Iron Ore Deposits in Brazilian Northern Region: Challenges and Strategies - Carlos Eduardo Soares Feliciano; Anderson Meireles; Leonardo Soares Chaves; Renato Jacome Costa; Raul Carretero Hoz (International Society of Explosives Engineers, 2025)
The large iron deposits in the northern region of Brazil located in the Amazon Craton have in common the presence of natural cavities. These cavities primarily occur in the upper layer of the ore body, formed above hematite mineralization. Their origin remains a topic of debate, often associated with hydrothermal drainage processes and erosive evolution. Over time, these cavities have become integral to the local environment, each contributing to the regional ecosystem of fauna, flora, and the significance of speleothems found within them. Managing these cavities poses a significant challenge for iron mines in the area. On one hand, they must preserve the cavities from anthropogenic actions, while simultaneously handling heavy equipment and large volumes. In 2023, the development of the mine took place towards the cavity under study, revealing systematic deviations in vibrations recorded during nearby detonations as the blasting got nearer. To address this, a work plan was put in place, emphasizing a straightforward approach: constructing lithology-specific vibration models, defining charge abacuses, and optimizing timing to reduce charge amplification. Implementing this methodology significantly improved adherence to the vibration limit, resulting in an around 50% reduction in standard error. This paper presents the consolidated work that allowed mining activities to continue in the area through controlled blasting, effectively mitigating potential anthropogenic damage in sensitive areas.